Ngereng Dhebu: Tinjauan Konstruksi Sosial-Edukatif Di Lingkungan Alumni Pesantren Madura - Syarifuddin, Muhammad; M. Mansyur (Al-Riwayah : Jurnal Kependidikan, 2024)
This research aims to determine the moments of internalization, objectification and externalization in forming the Ngereng Dhebu Culture for the Association of Alumni and Sympathizers (IKBASS) of the Miftahul Ulum Pannyeppen Pamekasan Islamic Boarding School. The approach used is qualitative with a case study type at the Miftahul Ulum Pamekasan Islamic boarding school. The data collection techniques used were interviews and observation with the data analysis technique being an interactive model. The results of this research show that the internalization of Ngereng Dhebu Culture for alumni at the Miftahul Ulum Panyeppen Pamekasan Islamic Boarding School is carried out with three main processes, namely acceptance, appreciation and practice. This moment is implemented through educational, learning and teaching activities. The moment of objectification in forming the "Ngereng Dhebu" culture is embedded in three aspects, namely knowledge about the value of obeying and obeying the kyai's orders as the essence of obtaining blessings and understanding between students, administrators and teachers regarding the mentoring and coaching process carried out in Islamic boarding schools as a form of character self-maturation. The externalization of Dhebu's Ngereng culture was formed when he was a student or an alumnus. The reflection of this expression has been shown in three dimensions, namely the behavioral dimension by presenting obedience and obedience. The linguistic dimension with the choice of subtle speech and the dimension of realizing meaning with a responsive attitude towards the existence of the kyai and